THEORY OF THE INFLUENCE OF TARGETING ON THE FORMATION OF CONSUMER CULTURE IN PRESCHOOL CHILDREN (Universal International Scientific Journal, 2026)
This article examines the impact of targeted advertising on the development of consumer culture in preschool-aged children. The relevance of the study stems from the widespread use of modern advertising technologies, which can significantly influence children's preferences and behavior, shaping immature consumer habits and increasing brand dependence. The aim of the study is to assess the level of preparedness of educators in understanding the principles of targeting and identifying ways to reduce the negative impact of advertising on children.
Keywords: targeting, consumer-economic values, consumer culture, preschoolers.